Manager-subordinate trust : a global perspective - Cardona, Pablo, 1964-; Morley, Michael (New York : Routledge, 2013)
"This volume in the Routledge Global Human Resource Management Series is dedicated to analyzing the process of trust development between managers and subordinates in different countries of the main cultures of the world. Behaviors and trust are linked in a process that can reinforce or diminish the trust between the two parties. This book examines that process in an array of countries, contextualizing each setting through a brief historical, institutional, and cultural overview and analyzing the universal and culturally-specific elements of the manager-subordinate relationship"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Industrial relations; Management; Electronic books